Dampak Bahasa dan Komunikasi Tiktok terhadap Perilaku Konsumen - Rida Ismiatul Aulia; Rara Meisi Azahra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The development of technology and social media, especially TikTok, has changed the way consumers interact with products and brands. This article aims to explore the impact of the language and communication used on TikTok on consumer behavior, especially in the context of impulse purchases. Through a qualitative approach, the study analyzed TikTok content that focuses on product promotion and how language and communication styles influence purchasing decisions. The results show that the use of engaging and communicative language on TikTok can increase buying interest and encourage consumptive behavior among users.